The sword of Judith : Judith studies across the disciplines - Brine, Kevin R.; Ciletti, Elena, 1948-; Lähnemann, Henrike (OpenBook Publishers, 2010)
The Book of Judith tells the story of a fictitious Jewish woman beheading the general of the most powerful imaginable army to free her people. The parabolic story was set as an example of how God will help the righteous. Judith's heroic action not only became a validating charter myth of Judaism itself but has also been appropriated by many Christian and secular groupings, and has been an inspiration for numerous literary texts and works of art. It continues to exercise its power over artists, authors and academics and is becoming a major field of research in its own right. The Sword of Judith is the first multidisciplinary collection of essays to discuss representations of Judith throughout the centuries. The collection includes new archival source studies, the translation of unpublished manuscripts, the translation of texts unavailable in English, and Judith images and music.